Do corpo, na filosofia de Friedrich Nietzsche - Ancona Lopez, Chiara (2017)
In this dissertation we propose a reflection on the philosophical role of the body in the production of thought and in the construction of knowledge. We will start from the body-soul duality introduced, at the beginning of Platonic philosophy, with epistemic purposes. We will investigate the deepening of this dichotomy as a result of the crystallization from an increasingly systematic exploration through philosophy and in the function of the advancement of Christianity which, appropriating this Platonic duality, derived in moral ramifications that radically split the Western man. We will try to follow the clues of the physiological motivations that led and lead men to accept this weakening perspective of singularities, adhering to the herd culture. We will reflect on the role of consciousness in maintaining this fracture. We will approach the relations of forces involved in this process and how much Nietzsche brought from the physiology, and more broadly from biology, scientific contents that gave physiological and discursive consistency to his perspective of the wills of power in permanent struggle in the multiplicity of organisms that compose the living body. We will ask with Nietzsche how the relations of domination in philosophical production are given, and why a certain force once imposed metaphysical rationality as a sure path to knowledge, banishing the body from this course and from that goal. After all, let us echo the philosopher's recommendation, repeated several times: to interrupt this cycle and to restart philosophy through the body